2020
DOI: 10.1101/2020.11.12.380931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Preclinical Inhibitor GS441524 in Combination with GC376 Efficaciously Inhibited the Proliferation of SARS-CoV-2 in the Mouse Respiratory Tract

Abstract: The unprecedented coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a serious threat to global public health. Development of effective therapies against SARS-CoV-2 is urgently needed. Here, we evaluated the antiviral activity of a remdesivir parent nucleotide analog, GS441524, which targets the coronavirus RNA-dependent RNA polymerase enzyme, and a feline coronavirus prodrug, GC376, which targets its main protease, using a mouse-adapted SAR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Four nucleoside analogues that are known inhibitors of SARS-CoV-2 replication were selected as reference for studies in HAEC cultures. These included remdesivir, GS-441524 ( Li et al, 2021 ; Pruijssers et al, 2020 ; Shi et al, 2020 ; Xie et al, 2020 ; Zandi et al, 2020 ) (the parent nucleoside of remdesivir), EIDD-1931 ( Zandi et al, 2020 ; Good et al, 2021 ; Sheahan et al, 2020 ) (the parent nucleoside of molnupiravir) and AT-511 ( Good et al, 2021 ) [a guanosine nucleotide analogue with activity against hepatitis C virus (HCV)]. To select a suitable concentration range of these molecules, we first explored their effect in VeroE6 and Huh7 cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four nucleoside analogues that are known inhibitors of SARS-CoV-2 replication were selected as reference for studies in HAEC cultures. These included remdesivir, GS-441524 ( Li et al, 2021 ; Pruijssers et al, 2020 ; Shi et al, 2020 ; Xie et al, 2020 ; Zandi et al, 2020 ) (the parent nucleoside of remdesivir), EIDD-1931 ( Zandi et al, 2020 ; Good et al, 2021 ; Sheahan et al, 2020 ) (the parent nucleoside of molnupiravir) and AT-511 ( Good et al, 2021 ) [a guanosine nucleotide analogue with activity against hepatitis C virus (HCV)]. To select a suitable concentration range of these molecules, we first explored their effect in VeroE6 and Huh7 cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with an earlier study ( Pruijssers et al, 2020 ), where the virus replication was monitored for 3 days. We demonstrated that the parent nucleoside GS-441524 ( Li et al, 2021 ; Pruijssers et al, 2020 ; Shi et al, 2020 ; Xie et al, 2020 ; Zandi et al, 2020 ) at 2 μM can also “sterilize” HAEC cultures from SARS-CoV2 as no rebound of the virus was noted several days after removal of the molecule. At 1 μM GS-441524, an intermediate antiviral potency was observed, but significant antiviral activity was not observed at 0.4 μM in the HAEC cultures.…”
Section: Discussionmentioning
confidence: 96%
“…GC-376 administered subcutaneously twice daily resulted in partial to full recovery in laboratory and client-owned cats infected with feline coronavirus [ 11 , 14 ]. In a mouse model of SARS-CoV-2 infection, intranasal and combined intranasal + intramuscular treatment with GC-376 only achieved marginal reduction in viral load [ 33 ]. The antiviral effect of GC-376 was improved when combined with GS441524, the parent nucleoside of the remdesivir prodrug.…”
Section: Pitfalls and Challenges In Assessing The Preclinical Antiviral Potency Of 3clpro Inhibitorsmentioning
confidence: 99%
“…Cathepsin L is involved in the entry of SARS-CoV-2 into host cells and therefore contributes to non-selective 3CLpro inhibitor potency in commonly used cell lines. GC-376, a broad spectrum inhibitor of 3C, 3C-like proteases and cathepsin L, failed to show a clear antiviral effect in monotherapy in a mouse model of SARS-CoV-2 infection [ 10 ]. In another study modest antiviral activity was observed in the K18-hACE2 SARS-CoV2 infection mouse model [ 11 ].…”
Section: Introductionmentioning
confidence: 99%